Identification of Hemolysine Genes and their Association with Antimicrobial Resistance Pattern among Clinical Isolates of Staphylococcus aureus in West of Iran - Hamid Motamedi; Babak Asghari; Hamed Tahmasebi; Mohammad Reza Arabestani (Advanced Biomedical Research, 2018)
Background: Staphylococcus aureus is expressing a broad range of different hemolysins enhancing its ability to establish and maintain infection in humans. The aim of this study was to identify the types of hemolysins in different clinical isolates of S. aureus and their association with antibiotic resistance patterns. Materials and Methods: In this cross-sectional and descriptive study, clinical isolates of S. aureus were collected from Hamedan's hospitals during an 11-month period from June 2016 to January 2017 and identified by using biochemical tests. To determine the antibiotic resistance pattern, disk diffusion method and minimum inhibitory concentration (MIC) were conducted. Genomic DNA was extracted using extraction kit. The polymerase chain reaction was done with specific primers for identification of hla, hlb, hld, and hld genes. Results: Among a total of 389 clinical samples, 138 isolates (35.45%) of S. aureus were identified, which 87 isolates (63.04%) were cefoxitin MIC of >4 μg/ml and resistant to methicillin. The highest frequency of antibiotic resistance was observed against erythromycin in 108 isolates (78.26%) and penicillin in 133 isolates (96.37%) and the lowest resistance was against gatifloxacin in 50 isolates (36.23%) and Cefazolin in 11 isolates (97.7%). Furthermore, the hla, hlb, hld, and hlg genes were detected among 11 (7.97%), 7 (5.07%), 16 (11.59%), and 4 (2.89%) isolates, respectively. There was a significant relationship between the presence of alpha and delta hemolysin-encoding genes and the antibiotic resistance pattern of isolates (P < 0.05). Conclusion: The results exhibited that the association between the presence of the hemolysin genes and the antibiotic resistance pattern can be considered as a serious issue.